Aktivitas Anti inflamasi Ekstrak Etanol Uwi Banggai Ungu (DioscoreaAlataL.) Terhadap Tikus Putih Galur Wistar Yang Induksi Putih Telur - Khaerati, Khildah; Rivani, Rivani; Ihwan, Ihwan (Jurnal Farmasi Indonesia, 2017)
ABSTRACT: Purple uwi Banggai (Dioscorea alata L.) is a plant used as a source of carbohydrates and also has many benefits. This research aimed is to know the dosage of ethanol extract of purple uwi Banggai which is effective as anti-inflammatory to white rat (Rattus norvegicus). This research used 25 test animals that were divided into five groups. All groups were induced with 100% egg whites with subplantar method, after 60 minutes each group was given different suspension. The negative control group was given a 0.5% Na CMC suspension, meanwhile positive control group was given 9 mg / 200 gBB mefenamic acid, and the third, fourth, and fifth groups were given test suspension with variation of doseÂ  200, 250, 300 mg / 200 gBB, then measured again inflammation volume with pletismometer for 6 hours with 60 minutes interval. Data were analyzed statistically using ANOVA. The result showed that the ethanol extract of purple uwi Banggai have anti-inflammatory effect on white rat induced egg white 100%. The effective dose as antiinflammatory is 200 mg / 200gBB.